2020
DOI: 10.1590/1980-5918.033.ao32
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional intervention and functional exercises improve depression, loneliness and quality of life in elderly women with sarcopenia: a randomized clinical trial

Abstract: Introduction: Loneliness interferes with the eating habits and functionality of the elderly, compromising their quality of life. Objective: This study aimed to evaluate the effects of eating and performing functional group-based exercises on depressive symptoms, loneliness and quality of life in patients with sarcopenia treated at a public health service. Method: This is a randomized clinical trial with a convenience sample of elderly women with sarcopenia according to the European Work Group of Sarcopenia o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
1
6
0
2
Order By: Relevance
“…The moderating effect of lower-extremity muscle strength on the relationship implies the clinical importance of both good nutrition and muscle fitness as a therapeutic strategy against late-in-life depression. In support of the current findings, Pinheiro et al [ 44 ] conducted a 12-week randomized control trial of sarcopenic elderly women and showed that a combination of nutritional intervention and group-based functional exercise is more effective at relieving depressive symptoms and social isolation, compared with a single intervention, such as nutritional intervention or socialization activities. In a cross-sectional study involving 130 community-dwelling Japanese older adults, Kaburagi et al [ 45 ] found that adequate nutritional status was positively associated with handgrip strength and maximum walking speed but negatively associated with GDS score, implying a pathologic connection between nutrition, physical fitness, and mental health.…”
Section: Discussionsupporting
confidence: 80%
“…The moderating effect of lower-extremity muscle strength on the relationship implies the clinical importance of both good nutrition and muscle fitness as a therapeutic strategy against late-in-life depression. In support of the current findings, Pinheiro et al [ 44 ] conducted a 12-week randomized control trial of sarcopenic elderly women and showed that a combination of nutritional intervention and group-based functional exercise is more effective at relieving depressive symptoms and social isolation, compared with a single intervention, such as nutritional intervention or socialization activities. In a cross-sectional study involving 130 community-dwelling Japanese older adults, Kaburagi et al [ 45 ] found that adequate nutritional status was positively associated with handgrip strength and maximum walking speed but negatively associated with GDS score, implying a pathologic connection between nutrition, physical fitness, and mental health.…”
Section: Discussionsupporting
confidence: 80%
“…33) Improvement in sarcopenia was also associated with better functional and discharge outcomes among patients with stroke undergoing rehabilitation. 34) Additionally, participants with recurrent stroke were more likely to have possible sarcopenia. However, this factor was only significant in the younger age group.…”
Section: Discussionmentioning
confidence: 99%
“… 33 ) Improvement in sarcopenia was also associated with better functional and discharge outcomes among patients with stroke undergoing rehabilitation. 34 )…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Verificou-se, por meio da aplicação desse protocolo às idosas sarcopênicas atendidas em serviço público de saúde, que a qualidade de vida e a preservação da capacidade funcional foram mais bem percebidas nos idosos que se exercitavam regularmente. 26 Os pacientes idosos que realizavam fisioterapia anteriormente à pandemia precisam continuar recebendo atendimento especializado no momento em questão. Para atender a essa necessidade, recomenda-se a opção de telemonitoramento como estratégia apropriada para prevenir o declínio funcional em idosos.…”
Section: Discussionunclassified